Post-Occupancy Evaluation of UK Library Building Projects: Some Examples of Current Activity - Enright, Suzanne (LIBER Quarterly: The Journal of the Association of European Research Libraries, 2002)
Post-occupancy evaluations of buildings ask questions and provide answers on how buildings actually work in technical, social and management terms for the end-users1. They can have a significant impact on creating change in terms of improving use of any building. Post-occupancy evaluations can show what works, and what does not – yet they are not common and apparently have been seldom done in a systematic way. Fortunately that picture is changing as post-occupancy evaluation becomes more action-orientated and more clearly based on addressing clients’ and architects’ needs. In the UK there are two formal schemes underway which have been applied to the Higher Education (HE) sector and to academic libraries – an external one led by the construction industry (PROBE or Postoccupancy Review of Buildings and their Engineering – which has undertaken over 100 studies to date) and the other, internal to the HE sector itself (led by the Higher Education Design Quality Forum). These are complimented by two 'softer’, qualitative forms of evaluation demonstrated by the efforts of (a) the library profession itself, led by SCONUL for academic libraries and by the Library Association for public libraries, and (b) the architecture and building related professions.